Developing early Age Children's Fine Motor Skills through Origami - Putra Efendi, Sandra; Mustika, Tiara; Milawati, Risna (Journal of Islamic Early Childhood Education, 2023)
The world of children is a world of imagination. Children have great curiosity when parents and teachers stimulate children with various skills. Children aged 5-6 years experience significant fine motor development when given interesting stimulation and exercises in class. Teachers experience problems in the art of paper folding to improve fine motor skills in early childhood. Teachers rarely train paper folding skills for early childhood because teachers are not yet skilled in the art of paper folding. The purpose of this community service is to improve children's fine motor skills through training in the art of paper folding. The art of paper folding can train children's fine muscles so that fine motor aspects in early childhood can be trained and improved. Through a pleasant experience for children when folding paper, it is possible to achieve fine motor development tasks in early childhood because learning will be meaningful through fun activities